592 Sentinel lymph node mapping in early-stage cervical cancer using near-infrared fluorescence imaging: a prospective pilot study. (14th December 2020) - Tranoulis, Anastasios; Awad, Hebatallah; Thompson, Christina; Fisher, Amy; Twigg, Jeremy
Abstract : Introduction/Background: The aim of this pilot study was to ascertain the feasibility of sentinel lymph node (SLN) mapping in early-stage cervical cancer (CC) and evaluate factors affecting bilateral SLN detection. Methodology: This was a prospective cohort study spanning the period from January 2015 to March 2019. Women with early-stage CC (FIGO 2018 stage IA2 to IB2) scheduled to undergo robot-assisted laparoscopic radical hysterectomy or trachelectomy and SLN mapping with the Da Vinci Si Surgical System with near-infrared (NIR) imaging and indocyanine (ICG) fluorescence detection were enrolled. All patients were given the choice of complete pelvic lymph node dissection and SLN mapping or SLN mapping only. Cervical injection with ICG (2 ml) was performed for all women. Side-specific lymphadenectomy was performed when mapping was unsuccessful. The detection rate was calculated. Plausible correlations amongst the variables were examined using the Spearman's correlation coefficient (rho) and multivariate logistic regression. Results: The study enrolled 47 women [mean age 41.83 (24–69) years; mean body mass index (BMI) 29.02 (19–48) Kg/m2], of whom 43 underwent robot-assisted laparoscopic radical hysterectomy, whilst four radical trachelectomy. 31 (65.95%) women were diagnosed with squamous cell carcinoma, while 13 (27.69%) with adenocarcinoma, 2 (4.25%) with adeno-squamous cell carcinoma and 1 (2.11%) with endometrioid carcinoma, respectively. In total, 76 SLNs were removed. SLNs were most commonly identified in the external iliac basins (68.4%), followed by the obturator fossa (21.05%), internal iliac basins (6.6%) and common iliac basins (3.95%), respectively. SLN detection rates were 87.23% per patient, 84.05% per heme-pelvis and 68.09% bilaterally. Lymph node metastasis was detected in 3 women (6.3%). There was no statistical correlation between bilateral SLN detection and age (rho=-0.09, p=0.63), BMI (rho=-0.08, 0.57), adenocarcinoma or adeno-squamous histological sub-type (rho=0.14, p=0.35), grade 3 (rho=-0.09, p=0.55) or tumour size > 2 cm (rho=0.19, p=0.21). None of these covariates were significant in multivariate analysis. Conclusion: Intra-operative SLN mapping using fluorescence imaging with ICG is feasible, yields high diagnostic accuracy and it can be considered as an alternative to complete lympadenectomy for carefully selected patients with early-stage CC. Disclosures: We certify that no party has a direct interest in the results of the research and that no benefit will be conferred to us or any organisation with which we are associated.